2018
DOI: 10.1021/acschembio.8b00026
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Engineering of Steroidogenic CYP260A1 for Stereo- and Regioselective Hydroxylation of Progesterone

Abstract: The production of regio- and stereoselectively hydroxylated steroids is of high pharmaceutical interest and can be achieved by cytochrome P450-based biocatalysts. CYP260A1 from Sorangium cellulosum strain So ce56 catalyzes hydroxylation of C19 or C21 steroids at the very unique 1α-position. However, the conversion of progesterone (PROG) by CYP260A1 is very unselective. In order to improve its selectivity we applied a semirational protein engineering approach, resulting in two different, highly regio- and stere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…Structure-guided rational design was conducted to mutate S326 to an asparagine, resulting in mutant S326R that displayed much better activity and selectivity for the formation of Best CYP106A2 mutants on progesterone. Relative values [%] of progesterone substrate and monohydroxylated products (15β-, 11α-, 9α-and 6β) produced by CYP106A2 WT mutants A395I and G395W/G397K, and best combinatorially derived mutants in 6 h whole-cell biotransformations with 200 μM of progesterone (Nguyen et al 2012) 1α-hydroxy-11-deoxycorticosterone compared to the WT parent (Khatri et al 2018).…”
Section: Cyp260a1: Cytochrome P450 From Myxobacterium Sorangium Cellumentioning
confidence: 99%
See 3 more Smart Citations
“…Structure-guided rational design was conducted to mutate S326 to an asparagine, resulting in mutant S326R that displayed much better activity and selectivity for the formation of Best CYP106A2 mutants on progesterone. Relative values [%] of progesterone substrate and monohydroxylated products (15β-, 11α-, 9α-and 6β) produced by CYP106A2 WT mutants A395I and G395W/G397K, and best combinatorially derived mutants in 6 h whole-cell biotransformations with 200 μM of progesterone (Nguyen et al 2012) 1α-hydroxy-11-deoxycorticosterone compared to the WT parent (Khatri et al 2018).…”
Section: Cyp260a1: Cytochrome P450 From Myxobacterium Sorangium Cellumentioning
confidence: 99%
“…In order to improve its regio-and stereoselectivity for progesterone transformation, Khatri et al cloned and expressed truncated protein of CYP260A1 (∆CYP260A1) (Khatri et al 2018), and the first 50 N-terminal residues were removed based on the alternative predicted gene transcript from the NCBI database (Khatri et al 2016a, b). Laborious efforts combining rational design and directed evolution were employed to create mutants of ∆CYP260A1 with improved regioselectivity towards progesterone hydroxylation (Khatri et al 2018). After recovery of complete activity of ∆CYP260A1, the substrate was docked into ∆CYP260A1 active site to explore potential hotspot residues.…”
Section: Cyp260a1: Cytochrome P450 From Myxobacterium Sorangium Cellumentioning
confidence: 99%
See 2 more Smart Citations
“…Such a map of the sequence‐function relationship was generated for the F87A template enzyme by analysing previous data from Commandeur et al ., Payne et al ., and their own lab, and by screening mutants available from a previous study . For example the group of Commandeur had identified residue 72 to be important for substrate orientation, and showed that it was completely inverting the stereoselectivity of C16 hydroxylation .…”
Section: Examplesmentioning
confidence: 99%